Penataan Peraturan Desa dalam Sistem Peraturan Perundang-undangan - Sirajuddin, Sirajuddin; Fatkhurohman, Fatkhurohman (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
Villages have actually been existing before the Republic of Indonesia was established, but in the journey of this Republic of Indonesia, they are often intentionally designed by the law-forming state elite. One of the main causes for the presence of the various portraits of the marginalization is the absence of respect, protection and the fulfillment of village community autonomy in our Constitution that has been amended 4 (four) times. This directly implies on the obscurity of the existence and position of village regulation and legal products in executing village authority and autonomy. The present research is aimed at (1) explaining the existence and position of village regulation in various legal products arranging the hierarchy of regulations; (2) finding a design of the setting of existence and position of village regulation in the hierarchy of the regulations based on the recognition and subsidiary principles in the village community autonomy. A normative juridical with an analytic descriptive specification based on the legal history and statutory approach. The result shows that the existence of village regulations will be recognized and they will possess a binding power if they are formed on the basis of the instruction of the higher regulation or authority. The village regulations, however, are made to reinforce and guard the subsidiarity and recognition principles-based village autonomy. In order to arrange the existence and the position of village regulations in the system of regulation, further changes of the Constitution have to accommodate the arrangement of village community autonomy. The existence and position of village regulatios should be strengthened in the statutory system in order to guard and reinforce village autonomy so that villages become autonomous and may maintain their local wisdom, economic and ecological sustainability, and their local wisdom-based economic growth.